2007
DOI: 10.1890/06-1901.1
|View full text |Cite
|
Sign up to set email alerts
|

Stream Ecosystem Functioning Under Reduced Flow Conditions

Abstract: Assessments of flow reduction in streams often focus on changes to biological communities and in-stream physical characteristics, with little consideration for changes in ecosystem functioning. It is unclear whether functional indicators of ecosystem condition may be useful for assessing the impacts of reduced discharge on small streams. Using weirs and diversions to reduce stream discharge during summer baseflow conditions, we tested the response of leaf breakdown, coarse particulate organic matter (CPOM) ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 54 publications
1
83
2
Order By: Relevance
“…To our knowledge, few other studies have examined the effects of reduced flow or drought on ecosystem functions. Dewson et al (2007) reported little influence on leaf breakdown rate by reduced discharge. However, their study was performed in New Zealand streams where specialized leaf-shredding taxa are rare.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, few other studies have examined the effects of reduced flow or drought on ecosystem functions. Dewson et al (2007) reported little influence on leaf breakdown rate by reduced discharge. However, their study was performed in New Zealand streams where specialized leaf-shredding taxa are rare.…”
Section: Discussionmentioning
confidence: 93%
“…5A). Correlational data on the effects of flow in running waters, however, are considerable, as it is a well-known central controlling variable in stream ecology (Beniston et al, 2007;Dahm et al, 2003;Daufresne et al, 2007;Dewson et al, 2007;Schindler and Donahue, 2006;Walters and Post, 2011) and a rich literature on the impacts of floods in lotic ecosystems has accrued since the 1980s, when there was a strong focus on understanding the role of flow refugia in determining community structure and dynamics (James et al, 2008;Statzner et al, 1988). Many of these studies are based on correlational field data, although some manipulative experiments and field bioassays were also conducted on the effects of (usually high) flow on the biota and their interactions (Gjerlov et al, 2003;Lancaster, 1996).…”
mentioning
confidence: 99%
“…Experiments have been advocated as useful tools to explore the impact of unpredictable extreme events in natural systems (Jentsch et al, 2007), but research on drought and low flows in streams has tended to be phenomenological (but see, e.g. Dewson et al, 2007b;Walters and Post, 2011) and based on field surveys that are often confounded by environmental gradients or which lack the pre-impact data necessary to demonstrate causation (James et al, 2008). In the present study, we simulated hydrologic drought in a series of stream mesocosms over 2 years to capture intra-and intergenerational responses to habitat loss caused by periodic dewatering of benthic habitat (see Ledger et al, 2008Ledger et al, , 2011Ledger et al, , 2012Ledger et al, , 2013.…”
mentioning
confidence: 99%